Особливості використання методу проектів у процесі вивчення учнями іноземної мови - Васюхник, Софія; Vasiukhnyk, S. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розкривається специфіка вивчення іноземних мов на сучасному етапі, яка полягає у тому, що у цьому процесі необхідно забезпечити усвідомлення учнями відмінностей у рідній та іншомовній культурі, формувати у них толерантне ставлення до представників інших народів та культур, навички іншомовної міжкультурної комунікації та готовності до діалогу культур, знижувати рівень етноцентризму. Встановлено, що для розв’язання цих завдань у учнів має бути сформована комунікативна компетентність, яка полягає у їхній здатності здійснювати іншомовну діяльність, володінні ними способами цієї діяльності і може бути забезпечена лише за умови наявності в учнів певного рівня лінгвістичної компетенції. Обґрунтовується, що ефективним шляхом її формування є використання у процесі вивчення учнями іноземної мови методу проектів, адже він передбачає активну пізнавальну діяльність учня у процесі навчання, спрямовану на оволодіння ним ефективними мовними засобами та навичками іншомовної мовної діяльності з урахуванням специфіки функціонування мови у тій чи іншій культурі. Використання цього методу найбільш повно забезпечує формування у учнів лінгвістичної, комунікативної компетенції поза мовним оточенням, забезпечує можливості опанування ним на практиці особливостей функціонування мови у тій чи іншій культурі і сприйняття мови як засобу міжкультурної взаємодії. The article reveals the specificity of studying foreign languages at the present stage, which consists in the fact that in this process it is necessary to ensure students' awareness of differences in their native and foreign language culture, to form a tolerant attitude towards representatives of other peoples and cultures, the skills of foreign-language intercultural communication and readiness for dialogue of cultures, reduce the level of ethnocentrism. It is established that to solve these problems the students should develop communicative competence, which is their ability to carry out foreign language activities, their own methods of this activity, which can be ensured only if they have a certain level of linguistic competence. It is substantiated that the effective method of its formation is the use of the project method in the process of learning by the pupils of a foreign language, because it provides for active cognitive activity of the student in the process of studying, aimed at mastering him with effective linguistic means and skills of foreign language activity taking into account the specific functioning of the language in one or another culture. It is analyzed that unlike communicative and role-playing technology and the technology of situational and linguistically oriented activities, which are widely practiced today in school in the process of studying foreign languages by pupils, the use of the project method is more productive, since it gives the teacher the opportunity to include students in real communication, research activity, the process of creating a new one, which requires the production of ideas, the search for non-standard ways, means, cooperation with others NITEL and translated into a real product of teamwork. It is established that the method of projects is most effective if to create conditions under which the student: independently extracts the necessary information for solving problems that arise in the course of the project; plans his actions and independently decides what materials he will need to carry out the tasks of the project and where he can find them; realizes himself in different situations of joint activity on the project with other students, performing different social roles (leader, performer, mediator and the like); uses different methods and methods of research; in the process of working on the project, usually communicates with other students and a teacher in a foreign language; shows cognitive creative activity; has the opportunity to realize themselves, regardless of the level of their own speech development, etc.
Use of the project method in the process of studying by students of a foreign language
Keywords: вивчення іноземної мови; метод проектів; особливості використання методу проектів у процесі вивчення учнями іноземної мови; foreign language study; project method; peculiarities of using the project method in the process of studying a foreign languagе